Parents’ Experiences on a Family Literacy Program in Finland - Aerila Juli-Anna; Kauppinen Merja; Siipola Mari (European Open Science Publishing, 2025)
In this article, we investigate a family literacy program called Bedtime Story Shelf, which is an application of lending libraries. In Bedtime Story Shelf-program the families are loaning books from ECE centers and schools to homes. In the study, we present parents’ prior (N = 122) on this program and its relation to families’ prior literacy practises. According to the results, almost all the families took advantage of the Bedtime Story Shelf-activity. However, about half of the families loaned books from the shelf more often. These families also evaluated the activity as more meaningful. They felt that loaning libraries enabled them to expand their knowledge of children’s books and made the children more active in family literacy events. These positive effects did not depend on the prior literacy practises of the family. This means that if we get the families involved in family literacy programs of ECEs and schools, they will find them beneficial. According to the study, one of the key objectives would be motivating the children and involving the parents. Furthermore, the educators should be active and flexible in their attempts to involve all the families.